372. Attributable Mortality of Candidemia After Introduction of Echinocandins. (26th November 2018) - Cornely, Florian; Cornely, Oliver; Koehler, Philipp; Koehler, Felix; Mellinghoff, Sibylle
Abstract: Background: Candidemia is among the most frequent nosocomial blood stream infections and associated with considerable morbidity and mortality. Landmark case–control studies estimated an attributable mortality of 38% and 49%. After introduction of echinocandins, attributable mortality may have decreased. Methods: In a case–control design, 100 consecutive, hospitalized patients with candidemia were enrolled at the University Hospital of Cologne. These cases had at least one blood culture positive for Candida spp. >48 hours post admission. We enrolled patients from January 2017 backwards until February 2014. Controls were patients without candidemia matched for age, sex, calendar year, duration of hospitalization, main admission diagnosis, and Patient Clinical Complexity Level. Risk factors for candidemia captured were malignancy, diabetes, infection other than candidemia, liver cirrhosis, hemodialysis, congestive heart failure, coronary artery disease, chronic lung disease, intensive care, mechanical ventilation, and presence of central lines. For each control patient, we considered the day of candidemia of its matched case to compare post diagnosis length of stay. We estimated attributable mortality until day 30 post candidemia diagnosis. We performed χ 2 -test for categorical and Student's t -test for continuous variables, and defined a two-tailed P -value of <0.05 statistically significant. Results: Cases and controls were 68% males. Median age was 62 and 63 years, and 25th and 75th percentile 55 and 74 years in both groups. Candidemia occurred a median 18 days post admission. For cases and controls, median length of stay post diagnosis was 17 and 15.5 days ( P = 0.13), for those controls who died 12 and 19 days ( P = 0.21), and for survivors 24 and 13 days ( P = 0.006). Day 30 mortality rates were 38% and 11% for cases and controls ( P = 0.03); thus attributable mortality was 27% (95% CI, 16%–28%). Conclusion: Attributable mortality of nosocomial candidemia is still substantial, but was lower in our study when compared with literature from before introduction of echinocandins. Disclosures: O. Cornely, Actelion, Amplyx, Arsanis, Astellas, AstraZeneca, Basilea, Bayer, Cidara, F2G, Gilead, GSK, Leeds University, Matinas, MedPace, Melinta, Merck/MSD, Miltenyi, Pfizer, Rempex, Roche, sanofi pasteur, Scynexis, Seres, Medicines Company: Research Contractor, Research grant and Research support. Allecra Therapeutics, Amplyx, Actelion, Astellas, Basilea, Cidara, Da Volterra, F2G, Gilead, IQVIA, Janssen, Matinas, Menarini, Merck/MSD, Paratek, PSI, Scynexis, Seres, Summit, Tetraphase, Vical: Consultant, Consulting fee. Astellas, Basilea, Gilead, Merck/MSD, Pfizer: Speaker's Bureau, Speaker honorarium.